The Impact of Genre and Familiarity on Reading Choices in College English for Students with Learning Challenges - Qi, Huan; Zhaoyan Meng; Yujing Dang; Yanni Xu; Meirong Yang (International Theory and Practice in Humanities and Social Sciences, 2025)
Purpose: With the continuous improvement of higher education penetration in China, college students group scale is also expanding, at the same time, lag behind, unable to adapt to the teaching situation of the learning student group is more and more large. This study examines how text genre and topic familiarity influence reading choices among college English students facing learning challenges. Approach: A total of 20 participants participated in this study (boys: n=9,18.85 ± 1.35 years old), Eyelink 1000plus device was used, participants freely scanned the articles on the screen and answered the corresponding questions to ensure that they had a comprehensive understanding of the content of the article. Four indexes of fixation duration, fixation counts, average fixation duration and average pupil size were analyzed. Results: The findings indicate that: 1) Students with learning challenges exhibit superior performance on expository texts compared to narrative and argumentative ones, with significantly reduced fixation duration and count on expository texts versus the other genres (p < 0.05); 2) These students demonstrate enhanced reading efficiency on English texts with known topics compared to those with unknown topics, characterized by notably lower fixation duration and frequency (p < 0.001). Conclusion: In light of these results, we propose the adoption of differentiated instruction, proceeding incrementally within the English curriculum to select suitable reading materials for students with learning challenges, aiming to enhance their reading proficiency and ameliorate their academic standing.